p63 inhibits CD44(+)/CD24(−) cell proliferation and chemoresistance in papillary thyroid carcinoma cells - Guo, Jing-Jing (Exp Ther Med, 2017)
Thyroid cancer typically has a good prognosis; however, the risks of recurrence and chemoresistance associated with thyroid cancer remain a cause for concern. Papillary thyroid carcinoma (PTC) comprises 80% of all cases of thyroid carcinoma. A previous study reported that cluster of differentiation (CD) 44(+)/CD24(−) PTC cells may contribute to PTC recurrence and chemoresistance; however, the underlying molecular mechanisms remain elusive. In the present study, CD44(+)/CD24(−) cells were isolated from the TPC-1 PTC cell line and biological function assays revealed that CD44(+)/CD24(−) cells were significantly more proliferative and chemoresistant compared with CD44(−)/CD24(−) cells. Furthermore, the expression level of p63 was demonstrated to be negatively correlated with the expression of CD44 in PTC cells. The role of p63 in CD44(+)/CD24(−) cell proliferation and chemoresistance was investigated and, the ectopic expression of p63 was observed to significantly inhibit CD44(+)/CD24(−) cell proliferation and chemoresistance in vitro and in vivo. In conclusion, the present study indicated that CD44(+)/CD24(−) cells contribute to PTC proliferation and chemoresistance and that the suppression of p63 in CD44(+)/CD24(−) cells contributes to these effects.